Macrophage Coordination of the Interferon Lambda Immune Response - Read, Scott A.; Wijaya, Ratna; Ramezani-Moghadam, Mehdi; Tay, Enoch; Schibeci, Steve; Liddle, Christopher; Lam, Vincent W. T.; Yuen, Lawrence; Douglas, Mark W.; Booth, David; George, Jacob; Ahlenstiel, Golo (Frontiers in Immunology, 2019)
Lambda interferons (IFN-λs) are a major component of the innate immune defense to viruses, bacteria and fungi. In human liver, IFN-λ not only drives antiviral responses, but also promotes inflammation and fibrosis in viral and non-viral diseases. Here we demonstrate that macrophages are primary responders to IFN-λ, uniquely positioned to bridge the gap between IFN-λ producing cells and lymphocyte populations that are not intrinsically responsive to IFN-λ. While CD14+ monocytes do not express the IFN-λ receptor, IFNLR1, sensitivity is quickly gained upon differentiation to macrophages in vitro. IFN-λ stimulates macrophage cytotoxicity and phagocytosis as well as the secretion of pro-inflammatory cytokines and interferon stimulated genes that mediate immune cell chemotaxis and effector functions. In particular, IFN-λ induced CCR5 and CXCR3 chemokines, stimulating T and NK cell migration, as well as subsequent NK cell cytotoxicity. Using immunofluorescence and cell sorting techniques, we confirmed that human liver macrophages expressing CD14 and CD68 are highly responsive to IFN-λ ex vivo. Together, these data highlight a novel role for macrophages in shaping IFN-λ dependent immune responses both directly through pro-inflammatory activity and indirectly by recruiting and activating IFN-λ unresponsive lymphocytes.